PENGARUH IKLIM TRANSFER TERHADAP MOTIVASI TRANSFER DAN TRANSFER PELATIHAN BAGI PARA PEGAWAI ADMINISTRATIF UNIVERSITAS JAMBI - Edward .; Sumarni . (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2013)
The purpose of this research is to examine the effect of transfer climate on transfermotivation and training transfer in context of climate transfer and training transfer. Data are collected from 176 respondents; they are administration employee of Jambi University.Data analysis useRegression both Simple and Multiple Regressions. Research result shows that there is mediating mechanism in contexet of Climate transfer and training transfer. Hence, it is could be concluded that the leader encourage employee to transfer their knowledge after training followed by creating organization climate condusively. Keywords: transfer climate, training transfer, motivation transfer.Â